2021
DOI: 10.1016/j.jns.2021.118656
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated sleep breathing disorders in a cohort of patients admitted to post-COVID-19 follow-up program: A single center experience

Abstract: Background and aimsHypersomnolence is a risk factor of ischemic stroke (IS), as well as one of its complications. We analyzed literature sources to study existing methods and neurotransmitters for diagnosing hypersomnolence in acute IS, and to assess the possibility and necessity of their use in this group of patients. MethodsWe reviewed 64 publications taken out from the databases PubMed, Embase, Frontiers, ResearchGate. ResultsCurrently, for the clinical and instrumental assessment of hypersomnolence disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There are very few data regarding OSAS in post‐COVID patients. To date, a few abstracts have reported rates of between 44% and 75% for newly diagnosed OSAS in pneumological patients with post‐COVID syndrome [16–18]. The percentage of OSAS cases among these patients is higher than that in our cohort.…”
Section: Discussionmentioning
confidence: 51%
“…There are very few data regarding OSAS in post‐COVID patients. To date, a few abstracts have reported rates of between 44% and 75% for newly diagnosed OSAS in pneumological patients with post‐COVID syndrome [16–18]. The percentage of OSAS cases among these patients is higher than that in our cohort.…”
Section: Discussionmentioning
confidence: 51%
“…According to our report, 83.64% of the applicants presented sleeping troubles, that is, insomnia below the threshold and at least moderate sleepiness. This is linked to the research done by (Angeli et al, 2021), where it was found that 68.1% of the study contestants had sleep disorders. A study did in Peru (Arteaga Poma, 2021) also showed that 91% of the participants presented insufficient sleep quality.…”
Section: Discussionmentioning
confidence: 90%
“…According to (Lima et al, 2020) it is expected that in the planet more than 30% of children and teenagers get sleep disorders and around 40% of teenagers have few hours of rest and are tired after waking up. This can cause the presence of various pathologies such as insomnia or drowsiness, which severely affect individuals sleep quality (Angeli et al, 2021). People contaminated with COVID-19 have registered great struggle in initiating or staying slept.…”
Section: Introductionmentioning
confidence: 99%